Discordant hormone receptor and human epidermal growth factor receptor 2 status in bone metastases compared to primary breast cancer. (November 2013) - Aurilio, Gaetano; Monfardini, Lorenzo; Rizzo, Stefania; Sciandivasci, Angela; Preda, Lorenzo; Bagnardi, Vincenzo; Disalvatore, Davide; Pruneri, Giancarlo; Munzone, Elisabetta; Della Vigna, Paolo; Renne, Giuseppe; Bellomi, Massimo; et al.
Abstract Background. In patients with metastatic breast cancer, the evaluation of the biological characteristics of metastatic bone deposits may be a valuable adjunct in clinical practice. We assessed the discordance in expression levels for estrogen receptor (ER), progesterone receptor (PgR) and human epidermal growth factor receptor 2 (HER2) between primary tumor and bone metastases and its clinical impact on patient management. Material and methods. We retrospectively reviewed 363 CT-guided bone biopsies performed from January 1997 to December 2009. The proportions of ER, PgR and HER2 positive tumors at primary diagnosis and bone metastases, determined by IHC and/or FISH, were compared using McNemar's test. The impact of the biopsy reassessment on treatment choice was evaluated with Fisher's exact test. Results. We selected 109 metastatic breast cancer patients with histologically confirmed bone metastases. Among 107 assessable patients the overall discordance rate was detected in 22 (20.5%) and in 47 (43.9%) patients for ER and PgR, respectively, and in six of 86 assessable patients (6.9%) for HER2 status. The indication to change endocrine therapy occurred in 62% and 30% of patients with ER discordance and ER concordance, respectively (p = 0.01). The indication to change targeted therapy occurred in 67% and 8% of patients with HER2 discordance and HER2 concordance, respectively (p = 0.002). Conclusions. We confirm that biopsy of metastases, including bone metastases, for reassessment of biology should be considered, since it is likely to impact on treatment choice.